Development of a Quantitative Model in Land Use Planning Using GIS - Masoud Masoudi; Parviz Jokar (REGION, 2022)
Land evaluation methods are crucial for evaluating the potentials and constraints of land for intended land use. In the procedure, environmental criteria such as topography, soil, climate, hydrology, and socioeconomic parameters are evaluated. Different technical procedures are also used for land evaluation ranging from simple methods based on expert knowledge to more complex methods based on simulation models. The main goal of this research is to evaluate land use and natural resources for future sustainable land planning using Geographic Information System (GIS). So, in this study, the Iranian ecological evaluation model was used for the analysis of the ecological and resources maps of the study area. First, ecological capability maps of different land uses such as forestry, agriculture, range management, environmental conservation, ecotourism, and development of villages, urban and industrial areas were developed by overlaying geographical maps based on Boolean overlay method (as a Multi-Criteria Evaluation Method) in GIS for the Township. The final step of this research was the prioritization of land uses considering the ecological and socio-economic characteristics (by distributing questionnaires to 63 experts (of the study area using a quantitative model. The results showed that the maximum area of proposed uses is 78.31%, which is related to rainfed agriculture, showing this land use has high potential and socio-economic demands in the study area. Meanwhile, minimum area of proposed uses is related to forest and ecotourism. One of the most important practical results of this study is that different or even modified methods should always be used in the same region to check the capability of land and the common method will not always be as best method.